Investigating drought index due to the climate change effect - Nurul Adzura Ismail, 1980-, author; Sobri Harun, author; Zaki Mat Amin, author; International Conference on Water Resources (2009: Langkawi) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL